The story of Prophet Zakariyya - Khan,saniyasnain (china goodwordbooks, 2024)
The story of Prophet Zakariya (Zachariah), as told in Islamic tradition, focuses on his unwavering faith, his humble nature, and his fervent prayer for a righteous son. Despite being elderly and his wife being barren, Zakariya's sincere supplication to Allah led to the miraculous birth of Prophet Yahya (John), who would also become a prophet. This story emphasizes the power of prayer, the importance of faith in Allah's divine plan, and the potential for miracles to occur even in seemingly impossible situations.
This book is from Islamic stories shelf:C R:1